Small-molecule fluorescence-based probes for aging diagnosis - Donglei Shi; Wenwen Liu; Guangwei Wang; Yuan Guo; Jian Li (Compuscript Ltd, 2022)
Aging is a time-dependent decline in physiological function that affects most organisms and is the major risk factor for many non-communicable diseases. The early diagnosis of aging is critical for the treatment of aging and aging-related diseases. In recent years, extensive efforts have attempted to accurately diagnose aging. To date, multiple types of fluorescent probes for various age-related biomarkers have been developed, with the aims of achieving rapid, precise diagnosis of the aging process and evaluating the efficacy of anti-aging drugs. This review summarizes recent research progress in small-molecule fluorescence-based probes for aging diagnosis, and further discusses the challenges and opportunities in this field.